1984
DOI: 10.1111/j.1469-7610.1984.tb01724.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Down's Syndrome Children Using the ‘Lock Box’: A Research Note

Abstract: A Lock Box for investigating problem-solving behaviour in pre-schoolers was used with seventeen Down's syndrome children (mean CA 37.4 months, S.D. 10.1 months) and seventeen 'normal' children (mean CA 37.4 months, S.D. 10.2 months) while their mothers were present. The behaviour was found to be different for the two groups, with the normal children showing greater competence, more organization and less perseverance. Significant associations between Lock Box measures and the mental age of the Down's syndrome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
1
4
1
Order By: Relevance
“…That MA is significantly associated with each of the two measures for competence and organization and with the relocking measures, replicates our previous results for the situation with mother involvement (Berry, Gunn & Andrews, 1984). The finding that the Down syndrome group was less competent in both unlocking and relocking and showed more aimless actions, even when MA is partialled out, may reflect a specific deficiency for Down's syndrome which is unrelated to mental age.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…That MA is significantly associated with each of the two measures for competence and organization and with the relocking measures, replicates our previous results for the situation with mother involvement (Berry, Gunn & Andrews, 1984). The finding that the Down syndrome group was less competent in both unlocking and relocking and showed more aimless actions, even when MA is partialled out, may reflect a specific deficiency for Down's syndrome which is unrelated to mental age.…”
Section: Discussionsupporting
confidence: 88%
“…Two methods of evaluating competence are employed, the first concerns the number of doors unlocked and the second the number of unsuccessful attempts to unlock the doors. In the present study, relocking behaviour has also been coded since an earlier investigation (Berry, Gunn & Andrews, 1984) had found that the number of doors relocked was significantly associated with competent performance. Organization scales refer to the child's patterns and sequences of behaviour while playing with the box.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study with preschoolers, Berry, Gunn and Andrews (1984b) found that the children with Down syndrome were less likely to try to lock a door than other children of the same mental age. In comparison with unlocking the door to remove a toy, there was no attempt to master the locking task.…”
Section: Syndrome-specific Characteristics and Education Programsmentioning
confidence: 99%